Methodological Approaches to Research Resource Saving Industrial Enterprises - Lopatin, Evgeniy (International Journal of Energy Economics and Policy, 2019)
Paper proposes the method of evaluating the performance of the company based on the use of production functions and factor models, which include the assessment of the entire apparatus and a set of performance indicators (appropriate) use of resources, resource saving. The method of assessing the performance depends on the use of the Cobb-Douglas production function. This function allows you to receive information about the appropriateness of the use of production resources, as well as timely carry out the correction of deviations of indicators of resources spent from standard values. Two-factor approach is using only the resources of labor expended and capital resources to calculate the required values. Keywords: energy, resource saving, industrial enterprises, Cobb-Douglas function, level of technical condition of production equipment, JEL Classifications: C30, D12, Q41, Q48 DOI: https://doi.org/10.32479/ijeep.7740